The Relationship between Fathers' Psychological Presence and the Formation of Anti-Bullying Attitudes at an Early Age: A Case Study of Assa'adah Kindergarten: Hubungan antara Kehadiran Psikologis Ayah dengan Pembentukan Sikap Anti-Bullying di Usia Dini: Studi Kasus TK Assa’adah - Farodisa, Salsabila Nur; Habibah⁠, Sulhatul; Nafisah, Aisyah Durrotun (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Bullying remains a recurring problem in educational settings, including early childhood education, where children are in a crucial stage of social and emotional development. Specific Background: Family plays a central part in preventing bullying, yet fathers’ roles are often overlooked because paternal involvement is frequently associated with economic responsibility rather than emotional caregiving. Knowledge Gap: Research on fathers’ psychological presence in shaping anti-bullying character in early childhood, particularly in early childhood education contexts, remains limited. Aims: This study examines the role of fathers’ psychological presence in forming anti-bullying character among young children at Assa’adah Kindergarten. Results: Using a qualitative case study, the findings show that fathers’ psychological presence appears through involvement in daily caregiving, warm communication, value transmission, and behavioral modeling. Anti-bullying character formation is reflected in children’s emotional control, empathy, self-confidence, assertive responses, and willingness to report harmful behavior without retaliation. Differences in paternal occupation shaped patterns of involvement, yet the quality of emotional engagement was more decisive than the amount of time spent together. Novelty: This study highlights fathers’ psychological presence as the central analytical focus and connects it directly with anti-bullying character formation in early childhood education. Implications: The findings support father-inclusive parenting programs and school-family collaboration as practical strategies for early bullying prevention. Highlights• Fathers’ psychological presence was reflected in caregiving, warm interaction, value transmission, and role modeling.• Anti-bullying character was shaped through emotional regulation, empathy, self-confidence, and safe reporting habits.• Emotional engagement mattered more than time quantity across different paternal occupational backgrounds. KeywordsFathers’ Psychological Presence; Anti-Bullying Character; Early Childhood Education; Emotional Engagement; Parenting Involvement